Obstacles Affect Perceptions of Egocentric Distances in Virtual Environments - Mine, Daisuke; Kimoto, Sakurako; Yokosawa, Kazuhiko (Frontiers in Virtual Reality, 2021)
Distance perception in humans can be affected by oculomotor and optical cues and a person's action capability in a given environment, known as action-specific effects. For example, a previous study has demonstrated that egocentric distance estimation to a target is affected by the width of a transparent barrier placed in the intermediate space between a participant and a target. However, the characteristics of a barrier’s width that affect distance perception remain unknown. Therefore, we investigated whether visual and tactile inputs and actions related to a barrier affect distance estimation to a target behind the barrier. The results confirmed previous studies by demonstrating that visual and tactile presentations of the barrier’s width affected distance estimation to the target. However, this effect of the barrier’s width was not observed when the barrier was touchable but invisible nor when the barrier was visible but penetrable. These findings indicate the complexity of action-specific effects and the difficulty of identifying necessary information for inducing these effects.